Nanoparticle Technology for Development of Immunostimulant Drugs Using Natural Product : Narrative Review - Seran, Yuvina (Indonesian Journal of Pharmaceutical Science and Technology, 2025)
The field of nanotechnology focuses on systems at the nanometer scale. Nanotechnology is used in the medical field for drug development, medical imaging, and gene therapy. One application of nanotechnology is nanoparticles. Nanoparticles have sizes in the nanometer range, with a scale of 1 to 100 nm. Nanoparticles can be designed to stimulate the immune system and improve the immune response. Literature study using research articles from national and international journals the application Publish or Perish 8 based on the keywords